2016
DOI: 10.1139/cjm-2015-0566
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of a “hockey-puck” phenotype to identify pilus and biofilm regulators in Serratia marcescens through genetic analysis

Abstract: Pili are essential adhesive determinants for many bacterial pathogens. A suppressor mutation screen that takes advantage of a pilus-mediated self-aggregative “hockey-puck” colony phenotype was designed to identify novel regulators of type I pili in Serratia marcescens. Mutations that decreased pilus biosynthesis mapped to the fimABCD operon; to the genes alaT, fkpA, and oxyR; upstream of the flagellar master regulator operon flhDC; and to an uncharacterized gene encoding a predicted DUF1401 domain. biofilm for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
0
14
1
Order By: Relevance
“…Fimbria or pili are adhesive organelles of bacteria and are important in establishment of infections. S. marcescens pilus production has been reported and linked to biofilm formation [37]. Genetic analysis showed that the type I pili which encoded by the operon fimABCD are essential for S. marcescens biofilm formation in early stages [38].…”
Section: Discussionmentioning
confidence: 99%
“…Fimbria or pili are adhesive organelles of bacteria and are important in establishment of infections. S. marcescens pilus production has been reported and linked to biofilm formation [37]. Genetic analysis showed that the type I pili which encoded by the operon fimABCD are essential for S. marcescens biofilm formation in early stages [38].…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of fimbria, which plays a role in cell-cell and cell-surface association 23 25 , did not impact predation. Thus, it could be concluded that fimbria does not serve as an attachment site nor could it interfere in the ability of the predator to reach any putative prey binding sites.…”
Section: Discussionmentioning
confidence: 91%
“… Strain Description Source or reference WT-K904 Clinical contact lens-associated keratitis strain 49 K904 fliC ::pMQ192 K904- Flagella mutant with fliC insertion mutation. 25 K904 fimC ::pMQ167 K904- Fimbriae mutant with fimC insertion mutation. 25 K904 phlA ::pMQ215 K904- Phospholipase-A with phlA insertion mutation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations